2015
DOI: 10.1111/hir.12097
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of knowledge brokering in health research: a systematised review with some bibliometric information

Abstract: Although this review shows that knowledge brokering has been an effective strategy for KT, it advocates for more empirical studies to compare the effectiveness of specific knowledge brokering approaches with others. It also calls for empirical studies to explicate the role of library and information science professionals in knowledge brokering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 37 publications
6
59
0
Order By: Relevance
“…Various studies have found it to be an effective strategy for knowledge mobilisation, but few are explicit about what aspects of the role are most effective. 190 Key questions are what types of brokering outcomes can and should be measured (e.g. increased evidence use, relationships and interactions between researchers and users, linkages and network, increases in capacity to use evidence) and how they can be adequately captured (e.g.…”
Section: Measuring Outcomes and Impactmentioning
confidence: 99%
“…Various studies have found it to be an effective strategy for knowledge mobilisation, but few are explicit about what aspects of the role are most effective. 190 Key questions are what types of brokering outcomes can and should be measured (e.g. increased evidence use, relationships and interactions between researchers and users, linkages and network, increases in capacity to use evidence) and how they can be adequately captured (e.g.…”
Section: Measuring Outcomes and Impactmentioning
confidence: 99%
“…In Elueze's review, their aim was to identify the effectiveness of knowledge brokering through a systematised review of the literature. In the 24 articles meeting the review inclusion criteria, they found that knowledge brokering has been an effective strategy for knowledge translation.…”
Section: In This Issue…mentioning
confidence: 99%
“…A review of studies evaluating knowledge transfer by Mitten et al [2] reports on the inadequate evidence base for evaluating knowledge transfer, its challenges and limitations, and calls for a rigorous evaluation of strategies. A recent review by Elueze [3] proposes the notion of intermediaries or bridges to support researchers in healthcare as ‘knowledge brokers’ to develop networks and relationships with, among and between producers and users of knowledge. By providing linkages, sources of knowledge, research evidence and marketing insights they can link researchers to users of research evidence enabling collaboration to identify issues, solve problems and promote evidence-informed decision-making in policy and practice.…”
Section: Introductionmentioning
confidence: 99%